2020
DOI: 10.3389/fpls.2019.01812
|View full text |Cite
|
Sign up to set email alerts
|

Increased Production of α-Linolenic Acid in Soybean Seeds by Overexpression of Lesquerella FAD3-1

Abstract: Soybean is a major crop that is used as a source of vegetable oil for human use. To develop transgenic soybean with high a-linolenic acid (ALA; 18:3) content, the FAD3-1 gene isolated from lesquerella (Physaria fendleri) was used to construct vectors with two different seed-specific promoters, soybean b-conglycinin (Pb-con) and kidney bean phaseolin (Pphas), and one constitutive cauliflower mosaic virus 35S promoter (P35S). The corresponding vectors were used for Agrobacterium-mediated transformation of imbibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 44 publications
(55 reference statements)
2
20
1
1
Order By: Relevance
“…The linolenic acid contents were significantly increased about 336%, 327%, and 327% in T10‐1, T11‐8, and T12‐1 lines, respectively compared with that in KA. In contrast to previous studies, 15 the oleic acid contents were not altered in PfFAD3‐1 lines. Linoleic and linolenic acids for PfFAD3‐1 lines were not within the ranges of the reference varieties.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…The linolenic acid contents were significantly increased about 336%, 327%, and 327% in T10‐1, T11‐8, and T12‐1 lines, respectively compared with that in KA. In contrast to previous studies, 15 the oleic acid contents were not altered in PfFAD3‐1 lines. Linoleic and linolenic acids for PfFAD3‐1 lines were not within the ranges of the reference varieties.…”
Section: Resultscontrasting
confidence: 99%
“…PfFAD3‐1 transgenic lines has an intentional change to the fatty acid profile compared to KA, producing a lower content of oleic and linoleic acids, and a higher content of linolenic acid, as a consequence of the overexpression of PfFAD3‐1 15 . In the current study, the levels of linoleic and linolenic were significantly changed between KA and three PfFAD3‐1 transgenic lines, indicating that the introduced PfFAD3‐1 gene has been successfully expressed (Table 8).…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…However, in most cases, it is difficult to find the desired trait in distant relatives. Hence, it is almost impossible to improve that trait through conventional breeding, i.e., improving Se contents in wheat and improving oleic and linoleic acid in the soybean (156,157). The unavailability of TOI in a species and its wild relatives is overcome through transgenic breeding.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Those reports also suggested that different plant embryos have various concentrations of tolerance to unusual fatty acids. Recently, seed-specific overexpression of Lesquerella FAD3 dramatically increased the C18:3 content and increased the seed size in soybean [127], while heterologous seed-specific overexpression of CsaFAD7 in the A. thaliana embryo showed the reverse phenotype. Those reports and findings imply that the production and accumulation of C18:3 showed various tolerance in A. thaliana and soybean.…”
Section: 4mentioning
confidence: 99%